Industrial training report: Hospital Canselor Tuanku Muhriz (HCTM) / Nur ‘Aainii Nabilah Mohamad Nasir - Mohamad Nasir, Nur ‘Aainii Nabilah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This industrial training report highlights my eight-week internship at the Public Health Unit of Hospital Canselor Tuanku Muhriz (HCTM), where I gained hands-on experience in information management, public health initiatives, and administrative tasks within a healthcare setting. My responsibilities included data collection, event coordination, report writing, and utilizing digital tools such as Canva and Autocrat to streamline workflows. I actively participated in organizing community outreach programs, designing promotional materials, and assisting in hospital-wide events, which enhanced my project management, teamwork, and problem-solving skills. Additionally, I attended seminars on patient confidentiality, healthcare administration, and professional ethics, which deepened my understanding of workplace standards and industry expectations. Despite challenges such as time management and adapting to new technical tools, I overcame them through strategic planning, collaboration, and continuous learning. This training significantly bridged the gap between theoretical knowledge and practical application, reinforcing the importance of accurate information management, organization, and effective communication in the healthcare industry. The experience has equipped me with valuable skills and insights that will be instrumental in my future career, particularly in managing healthcare data, enhancing public health initiatives, and contributing to efficient hospital operations.